2017
DOI: 10.4081/cp.2017.987
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota’s Effect on Mental Health: The Gut-Brain Axis

Abstract: The bidirectional communication between the central nervous system and gut microbiota, referred to as the gut-brain-axis, has been of significant interest in recent years. Increasing evidence has associated gut microbiota to both gastrointestinal and extragastrointestinal diseases. Dysbiosis and inflammation of the gut have been linked to causing several mental illnesses including anxiety and depression, which are prevalent in society today. Probiotics have the ability to restore normal microbial balance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
254
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(285 citation statements)
references
References 65 publications
0
254
0
5
Order By: Relevance
“…Mice receiving IBS‐D stool also showed different serum metabolomic profiles associated with faster GI transit, intestinal barrier dysfunction, and innate immune activation . Furthermore, disturbed microbiota profiles are associated with co‐morbidities of IBS, including cognitive changes, anxiety, and depression . These studies indicate the gut microbiota's potential to contribute to IBS symptoms as well as to serve as a therapeutic target.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Mice receiving IBS‐D stool also showed different serum metabolomic profiles associated with faster GI transit, intestinal barrier dysfunction, and innate immune activation . Furthermore, disturbed microbiota profiles are associated with co‐morbidities of IBS, including cognitive changes, anxiety, and depression . These studies indicate the gut microbiota's potential to contribute to IBS symptoms as well as to serve as a therapeutic target.…”
Section: Introductionmentioning
confidence: 88%
“…15 Furthermore, disturbed microbiota profiles are associated with co-morbidities of IBS, including cognitive changes, anxiety, and depression. 16 These studies indicate the gut microbiota's potential to contribute to IBS symptoms as well as to serve as a therapeutic target. In this brief review, we summarize the gut microbiotabased treatments of IBS, including prebiotics, probiotics, antibiotics, diet, and FMT.…”
Section: Introductionmentioning
confidence: 90%
“…The observed links between disturbance of the gut microbiome (dysbiosis) and stress, anxiety, and depression have shifted the research ground for mental disorder [12,44,45]. In response to these emerging findings, probiotics and dietary approaches have been explored in terms of their ability to modulate microbiota and address symptoms [46].…”
Section: Getting Out Of the Head: Guts And Mental Healthmentioning
confidence: 99%
“…However, in recent years, research into the microbiome–gut–brain axis has foregrounded the impact of the gut microbiome on mental health [10], inverting these dominant top-down models of mental illness. This emerging evidence, which shows observable links between gut dysbiosis and some mental health conditions, suggests that mental health is not all about the head, after all, leading to some paradigm shifting interpretations and conclusions about what is actually meant by ‘mental’ health, and how it should be treated [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Even in 2011, it was still located in the hypothetical realm [2]. Almost a decade later, more clinical trials are needed on humans, as is pointed out in recent reviews [3,4], and the precise nature of the process is still not known. But numerous studies have demonstrated clear links between intestinal microbiota and mood, behaviour, and cognitive impairment [58] and such findings could have radical implications for the treatment of neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%